SISTEM INFORMASI DESA DURIAN BESAR BERBASIS WEB - Surya Ade Saputera; Kirman Kirman; Yetman Erwadi; Lutame Al Fajarian (Jurnal Media Infotama, 2024)
In a very modern era like today where life is already in the era of the industrial revolution or commonly known as the digital era which includes information technology as part of human life in accelerating and facilitating the delivery of information, for example websites. The problem that occurs is that Durian Besar Village does not yet have a website as a means of conveying information to the public quickly and efficiently as a form of transparency on what the village government has done. The effect is that the community also experiences difficulties in obtaining information by having to come and meet sources of information, in this case the village government. The website was successfully built by presenting a member page feature to the public in which there are complaints and correspondence features. In this way, on this website, besides the community being able to access information easily, the community can also send messages or submit letters to the village government easily without having to come to the village office. The website is built with WordPress cms and also uses the Ultimate Member, WpForms and Elementor Pro add-ons for the appearance design.